A Propensity Score-Based Analysis of Laparoscopic Liver Resection for Liver Malignancies in Elderly Patients - Amr Badawy; Satoru Seo; Rei Toda; Hiroaki Fuji; Ken Fukumitsu; Takamichi Ishii; Kojiro Taura; Toshimi Kaido; Shinji Uemoto (Journal of Investigative Surgery, 2019)
Purpose: Laparoscopic liver resection is safe, feasible and associated with less blood loss, shorter hospital stays and fewer postoperative complications in the working age patients with malignant liver tumors. However, it is still unclear if the elderly patients with malignant liver tumors would also benefit from that approach as the younger patients. So, the aim of the study was to compare the clinical outcomes of laparoscopic versus open liver resection for malignant liver tumors in elderly patients. Materials and Methods: Between March 2009 and July 2016, all elderly patients (≥70 years old) who underwent laparoscopic (n = 40) and open (n = 202) liver resection for malignant liver tumors were included. A one to one propensity score matching analysis was performed, based on 6 covariates, to decrease the selection bias. Results: There was no significant difference between the laparoscopic and open liver resection groups regarding the patient characteristics and tumor features. The operative time was comparable between both groups (Laparoscopic group 259 min vs Open group 308 min, p = .86), while patients who underwent laparoscopic liver resection had lower intraoperative blood loss (30 ml vs 517 ml, p < .0001), shorter hospital stays (10 days vs 23 days, p < .0001), and less overall morbidity (15% vs 38%, p = .04). The one-, three-, and five-year survival for patients with hepatocellular carcinoma was comparable between both groups (Laparoscopic group 96%, 74%, 47%, vs Open group 94%, 71%, 48%, p = .82), whereas The one-, three-, and five-year recurrence-free survival for patients with hepatocellular carcinoma was significantly higher in the laparoscopic group (88%, 60%, 60% vs 54%, 25%, 19%, p = .019). Conclusions: Laparoscopic approach for minor liver resection in elderly patients is safe and feasible with less blood loss, a shorter hospital stay, less postoperative complications and a better oncological outcome.